Pengaruh Penambahan Jahe Merah (Zingiber officinale var. rubrum) Terhadap Mutu Organoleptik dan Biokimia Ikan Bandeng (Chanos chanos) Presto Selama Penyimpanan Dingin - Dian Iriani; Tjipto Leksono; Wika Romauli br Hutahayan (Jurnal Teknologi dan Industri Pertanian Indonesia, 2022)
Red ginger is a spice that can extend the shelf life of fish because it contains an antibacterial compound. This study was aimed to determine the effect of red ginger on the organoleptic and biochemical quality of presto milkfish during cold storage. The method used in this research was an experimental method, which was processing milkfish presto with the addition of red ginger with different concentrations (0% (J0), 60% (J1), 70% (J2), and 80% (J3)) during cold temperature storage using a non-factorial randomized block design with the length of storage (0, 3, 6, and 9 days) as replication group. The parameters observed were organoleptic analysis (appearance, odor, taste, and texture), microbiological analysis (total plate count and viability of Staphylococcus aureus) and chemical analysis (moisture content, water activity, and pH). Based on the result, the addition of 70% of the red ginger extract was the best treatment (J2) with the characteristics of hedonic quality are appearance 7,3 (neat, clean, and have a luminous golden yellow color), odor 7,5 (very fresh and fragrant odor of red ginger), taste 7,2 (tasty, savory, soft spines), texture 7,6 (flexible texture, dense, and compact). Meanwhile, the total plate count was 3,7 x 105 colonies/gram and there were no Staphylococcus aureus bacteria during 6 days storage. Moreover, it had 58,72% of moisture content, 0.70 of water activity and 6.15 of pH.